2018
DOI: 10.1002/ptr.6105
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effect of lambertianic acid through AMPK/FOXM1 signaling in MDA‐MB231 breast cancer cells

Abstract: Though lambertianic acid (LA) was known to exert antitumor effect in liver and prostate cancers, its underlying anticancer mechanism is never reported in breast cancers so far. Thus, in this study, apoptotic mechanism of LA was elucidated in MDA-MB-231 breast cancer cells. Here, LA increased cytotoxicity in MCF-7 and MDA-MB-231 cells; enhanced sub-G1 population, G2/M arrest, and cleaved poly(ADP-ribose) polymerase; activated phosphorylation of AMP-activated protein kinase (AMPK)/acetyl-CoA carboxylase pathway;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
(44 reference statements)
4
15
0
1
Order By: Relevance
“…Since the 24-AMPK-gene set was a positive prognostic factor in glioma where high expression of the genes was associated with better outcomes ( Figure 2C), glioma patients harboring low AMPK scores and high oncogenic TF scores performed the worst. Our results are confirmed by other reports on the crosstalk between AMPK signaling and E2F4, EZH2, FOXMI or SUZ12 and their effects on oncogenic progression (42)(43)(44)(45). Our analyses on SMAD4 in glioma revealed a likely tumor-suppressive role of the gene ( Figure 6B), which is corroborated by another study demonstrating reduced SMAD4 expression during glioma tumor progression (46).…”
Section: Discussionsupporting
confidence: 91%
“…Since the 24-AMPK-gene set was a positive prognostic factor in glioma where high expression of the genes was associated with better outcomes ( Figure 2C), glioma patients harboring low AMPK scores and high oncogenic TF scores performed the worst. Our results are confirmed by other reports on the crosstalk between AMPK signaling and E2F4, EZH2, FOXMI or SUZ12 and their effects on oncogenic progression (42)(43)(44)(45). Our analyses on SMAD4 in glioma revealed a likely tumor-suppressive role of the gene ( Figure 6B), which is corroborated by another study demonstrating reduced SMAD4 expression during glioma tumor progression (46).…”
Section: Discussionsupporting
confidence: 91%
“…This might have been responsible for the greater pro-apoptotic influence of AICAR in MDA-MB-231 cells. This was also consistent with the reported apoptotic influence of AMPK activation in MDA-MB-231 cells, which was mediated by inhibition of Akt/FOXM1 signalling (Lee et al, 2018). Cell cycle analysis in T47D cells showed that AICAR-activated AMPK affected cell proliferation by induction of both cell cycle arrest and apoptosis ( Figure 5).…”
Section: Discussionsupporting
confidence: 90%
“…In fact, the AMPK signaling pathway has been proved to be strongly linked to various tumors such as HCC. 24,25 Further study of gene expression in the HCC database from the TCGA website ( Figure 1D) revealed that the Rab10 gene was highly expressed in multiple stages of HCC, which matched the observations from Rab10 gene expression in the GSE49515 microarray data. To further understand the upstream regulatory mechanisms of the Rab10 gene, databases such as miRDB were used to predict regulatory miRNAs for Rab10.…”
Section: The Role Of Rab10 As An Oncogene In Hccsupporting
confidence: 71%